Wisdom of Landscape Construction of China’s West Lakes in Historical Period and Its Implications - Lyuyuan Jia; Qing Lin; Xiyue Wang; Wenzhen Jia; Ying Zhao; Zhiqing Zhang; Ziqi Cui; Song Chen; Aibo Jin (Land)
West Lake holds a significant position internationally. This article studies the spatial distribution, historical development, functions, and the lake–city spatial relationship of 81 West Lakes (WLs), as well as their landscape characteristics. The results indicate the following: (1) The overall spatial distribution of WLs is related to China’s history of water conservancy development. (2) The evolution of and functional changes in WLs are influenced by multiple factors such as politics, economy, and culture during different historical periods and are directly related to the will of local administrators. (3) The initial functions of WLs can be categorized into three types, primarily related to urban infrastructure. (4) In terms of spatial relationships, there are four types of spatial relationships between WLs and their water sources and three types of spatial relationships between WLs and cities, forming a common pattern of “Mountains/Hills(–Water)–WL(–Water)–Cities(–Water, River, Sea)” or “WL(–Water)–Cities(–Water, River, Sea)”. (5) The scenery of WLs comprises six elements, including natural basements, water conservancy facilities, human settlements, secularization, landscape architecture, and animal and human activities, all imbued with poetic cultural connotations. Furthermore, this study summarizes three causes of WLs’ scenery; excavates the historical wisdom of WLs in terms of a holistic approach, ecological techniques, dynamic management, and landscape esthetics; and subsequently proposes recommendations for lake ecological governance and landscape construction.